BULI LATERITIC NICKEL DEPOSITS HALMAHERA : FROM PROSPECTING TO RESERVES ESTIMATION - EP. Setyaraharja; T. Sutioso; L. Efendi (Jurnal Ilmiah MTG, 2012)
Nickel is one of the mineral commodities targeted by Antam. In searching the nickel potential, Antam has reviewed the Maluku area which previously explored by Indeco, including Halmahera. Antam holds 2 ( two ) licences for nickel in the Buli area, Halmahera : one is at mining stage and the other one is at exploration stage.Tectonically, Halmahera Island forms a geologic complex area, as it is located in the junction of the Eurasian, Pacific and Indo_Australian plates. The complexity is represented by obducted oceanic crust and presence of major transcurrent faults . As a result of the obduction, ophiolitic units and associated oceanic sediments are exposed in the eastern part of Halmahera.Laterite nickel at Buli is due to lateritization of the ultramafic rocks, part of the ophiolitic units, and leave the stable minerals such as nickel, cobalt, cromium, iron and alumina. Through a systematic landsat interpretation, mapping and sampling,starting in 1989, prioritised areas had been selected. These areas have then been followed up by geophysical surveys, test pitting and drilling.As a result, 3 ( three ) lateritic nickel deposits had been defined at Gee island, Tanjung Buli and Mornopo. The first two deposits have been mined since 1997 and 2001 respectively. While the third deposit will be inaugurated soon. In additon one prospect had also been identified at Sangaji. The deposits comprise 2 ( two ) types of ore : limonite and saprolite. Cutoff grade for them are 1.2 % Ni and 1.6 % Ni respectively. As of December 2004, the total reserves and resources of the saprolite type deposits : are estimated to be 31.4 million tons @ 2.40 % Ni and 25.0 million tons @ 2.40 % Ni respectively. While the limonite type deposits contain the reserves of 10.9 million tons at 1.50 % Ni & 0.18 % Co and the resources of 87.5 million tons at 1.47 % Ni & 0.18 % Co. There is another resources of 33.0 million tons grading 1.40 % Ni and 0.19 % Co at Sangaji.Antam has always been mining the high grade materials of both saprolites and limonites, and shipped it to Pomalaa , Japan and Australia for further processing. The low grade materials are being thought. Apart from blending, a hydrometallurgical process is being considered.